To what extent does IQ 'explain' socio-economic variations in function? - van Eijk Jacques; Kempen Gertrudis IJM; van Boxtel Martin PJ; Bosma Hans; Jolles Jelle (BMC, 2007)
Abstract Background The aims of this study were to examine the extent to which higher intellectual abilities protect higher socio-economic groups from functional decline and to examine whether the contribution of intellectual abilities is independent of childhood deprivation and low birth weight and other socio-economic and developmental factors in early life. Methods The Maastricht Aging Study (MAAS) is a prospective cohort study based upon participants in a registration network of general practices in The Netherlands. Information was available on 1211 men and women, 24 - 81 years old, who were without cognitive impairment at baseline (1993 - 1995), who ever had a paid job, and who participated in the six-year follow-up. Main outcomes were longitudinal decline in important components of quality of life and successful aging, i.e., self-reported physical, affective, and cognitive functioning. Results Persons with a low occupational level at baseline showed more functional decline than persons with a high occupational level. Socio-economic and developmental factors from early life hardly contributed to the adult socio-economic differences in functional decline. Intellectual abilities, however, took into account more than one third of the association between adult socio-economic status and functional decline. The contribution of the intellectual abilities was independent of the early life factors. Conclusion Rather than developmental and socio-economic characteristics of early life, the findings substantiate the importance of intellectual abilities for functional decline and their contribution - as potential, but neglected confounders - to socio-economic differences in functioning, successful aging, and quality of life. The higher intellectual abilities in the higher socio-economic status groups may also underlie the higher prevalences of mastery, self-efficacy and efficient coping styles in these groups.